Analisis Penyerapan Anggaran Pemeliharaan Jalan Pasca Penerapan Kebijakan Earmarking Tax Atas Pajak Kendaraan Bermotor di Provinsi Banten. - Yuliari, Nilan Cahya; Minan, Jeni; Aditya, Toddy (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
Regional governments have an important role in the development of their own regions and must have the ability to increase revenue and optimize the effectiveness and efficiency of budget use in order to improve public services to the community. Budget performance can be measured through the level of budget absorption. In increasing accountability for the use of budget revenues, the Banten provincial government issued Regional Regulation No. 1 of 2011 concerning Regional Taxes with reference to Law No. 28 of 2009 which includes the concept of earmarking tax. The regulation states that 10% of motorized vehicle tax is allocated for the construction, maintenance of roads and public transportation. The purpose of implementing this earmarking tax is to gradually and continuously improve the quality of service and create good governance and clean government. This research method uses a qualitative research method with a descriptive approach. The results of this research are road maintenance with a minimum of 10% of the profit sharing of motorized vehicle tax in Banten province which has exceeded the predetermined minimum limit and has been absorbed. Total earmarking funds reached 50.01% of road maintenance costs and road maintenance expenditures reached 19.99% of total Motor Vehicle Tax revenues which were shared into the Banten Province treasury.